the given equation can be written as:
"\\frac{y'}{\\sqrt{y}}+ \\frac{x\\sqrt{y}}{(1-x^2)} = x"
let "v=2\\sqrt{y}"
then, "v'=\\frac{y'}{\\sqrt{y}}"
substituting above, we get,
"v'+ \\frac{xv}{2(1-x^2)} = x" ........(1)
comparing with v'+Pv=Q where P and Q are functions of x
P= "\\frac{x}{1-x^2}" and Q= x
integrating factor= "e^{\\int{Pdx}}= e^{\\int{\\frac{x}{(1-x^2)}dx}} = (1-x^2)^{-1\/4}"
multiplying (1) by integrating factor,
"v. (1-x^2)^{-1\/4} = \\int{(1-x^2)^{-1\/4}.x}dx"
"v. (1-x^2)^{-1\/4} = -\\frac{2}{3}(1-x^2)^{3\/4} + c"
substituting value of v,
"2\\sqrt{y}. (1-x^2)^{-1\/4} = -\\frac{2}{3}(1-x^2)^{3\/4} + c"
"2\\sqrt{y}= -\\frac{2}{3}(1-x^2) + c(1-x^2)^{1\/4}"
now, y(0)=1
"2=\\frac{-2}{3}+c \\\\\n\nc=\\frac{8}{3}"
"2\\sqrt{y}= -\\frac{2}{3}(1-x^2) + \\frac{8}{3}(1-x^2)^{1\/4}"
Comments
Leave a comment